2020
DOI: 10.47895/amp.v54i2.1504
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Knowledge, Attitudes, and Practices of Healthcare Practitioners in Rizal Province, Philippines toward Implementing the Universal Newborn Hearing Screening Program

Abstract: Objective. The study describes the current knowledge, attitudes, and practices of healthcare practitioners in Rizal province regarding the implementation of the universal newborn hearing screening program (UNHSP).Materials and Methods. A descriptive phenomenologic research design through focus group discussions with pediatric and OBGYN consultants in a government hospital, nurses from private primary and secondary hospitals, midwives from private birthing homes, and rural health workers.Results. Attitudes. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The current study aimed to characterize the implementation of UNHSP in Rizal province and Northern California. As with previous findings 30 , there is a significant need to disseminate information about newborn hearing screening among healthcare practitioners, including clear roles in implementing the program and directories for confirmatory diagnosis and intervention. This is in conjunction with the lack of regional surveillance data that can be the basis for innovations and interventions for service delivery.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The current study aimed to characterize the implementation of UNHSP in Rizal province and Northern California. As with previous findings 30 , there is a significant need to disseminate information about newborn hearing screening among healthcare practitioners, including clear roles in implementing the program and directories for confirmatory diagnosis and intervention. This is in conjunction with the lack of regional surveillance data that can be the basis for innovations and interventions for service delivery.…”
Section: Discussionmentioning
confidence: 60%
“…"So sabi ng isang ano na-attendan ko na Pedia, dapat daw since mahal naman daw talaga yang Hearing Test na yan, turuan nalang daw mga midwife na pumalakpak." (A pediatrician in a seminar I attended told us that since newborn hearing screening is expensive, midwives should be taught to clap instead) -49, female, Midwife, and Birthing Home Owner Building upon the findings by Rozul, Gregorio, and Chiong's 30 , one of the prevalent challenges in Rizal include the lack of specific knowledge on implementing UNHSP; this includes knowledge on risk factors, age of hearing detection, stop criteria, submission of records to NHSRC, and referrals after the detection of hearing loss. Participants of the FGD suggested the provision of directories of diagnostic and intervention centers and fact sheets.…”
Section: Challenges and Solutions In Rizalmentioning
confidence: 99%
“…These require mid-level cognitive processing (application and analysis). 45,46 Rozul, Yarza, and Ombao 22,47 emphasized the importance of the mastery of these key concepts as a competency of screeners, adding weight on assigned points for these items in the online adaptation of the NHS certification course. In practical applications, it is best measured as a procedural skill.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with another local study, which reported lack of knowledge on the rationale and implementation of the UNHSI program among healthcare practitioners. 14 These findings are not surprising. Whilst the DOH (and the NHSRC) through its regional offices, might have campaigned for the UNHSI program, these RHUs were not enabled with capacity for NHS (no investments in training screeners, absence of NHS equipment).…”
Section: Accessible Care; Presence Of a Confirmatory Testing Center W...mentioning
confidence: 92%